The contribution of irrigation water and growth substrate for microbial flux in a vertical farm - Erskine, Elliot; Skinner, Niall; Holden, Nicola (Letters in applied microbiology, 2025)
Controlled environmental agriculture (CEA) is an emerging technology with increasing adoption for commercial applications. However, its impact on the plant microbiome is not entirely clear. The assumption is that controlled conditions reduce the risk of introduction and spread of pathogens, human or plant. Here, we assessed the microbial flux through a commercially relevant CEA plant growth tower from culture-dependent and independent approaches. This allowed the relationship between two of the main entry points for microbes to be determined, the circulating water system and plant growth substrates, on two crop species systems, kale and lettuce. There was a clear distinction between the taxonomic compositions of bacteria in the water-associated and coir-associated compartments. Overall, water did not contribute the most abundant members of the microbiota on plants. Rainwater, used as a top-up source of water, was not the major source of sequenced microbes in either the circulating water system or in coir compartments. The main points of expansion of cultural microbes were in the irrigation tray system and the physical presence and growth of the crop plants. The effect of UV-C, typically used to treat water, and the LED lighting system were quantified for proxy pathogen strains.